Detection of Extended- Spectrum Beta-Lactamase producing Escherichia coli from mesenteric lymph nodes of wild boars (Sus scrofa) - Silvia Bonardi; Clotilde Silvia Cabassi; Simona Longhi; Federico Pia; Margherita Corradi; Stefano Gilioli; Erika Scaltriti (Italian Journal of Food Safety, 2019)
Wild boars (Sus scrofa) are increasing in several European countries, including Italy. In areas with intensive animal farming, like the Italian Emilia-Romagna region, they are likely to be exposed to antimicrobialresistant (AMR) bacteria of livestock origin. In 2017-2018, 108 mesenteric lymph nodes samples were collected from 108 wild boars hunted in Parma province, Emilia-Romagna region, to be tested for ESBL- and carbapenemase-producing Escherichia coli. One isolate (WB-21L) out of 108 (0.9%) was phenotypically confirmed as ESBLproducing E. coli. The strain WB-21L was tested by PCR for the genes blaSHV, blaCTX-M, blaTEM, blaAmpC, blaKPC, blaNDM, blaVIM, blaIMP, blaOXA-48, blaSPM, blaBIC, blaSIM, blaDIM, blaGIM, blaAIM, resulting positive for TEM β-lactamase. Resistance to ampicillin, amoxicillin/clavulanic acid, streptomycin, sulfasomidine, tetracycline and trimethoprim confirmed the multi-resistance nature of the strain WB-21L. Nine E. coli isolates showed resistance to meropenem by the Kirby Bauer test but none of them showed Meropenem MIC values indicative of resistance. In conclusion, the present study shows the presence of ESBL E. coli in wild boars and the possible risk of transfer to game meat handlers and consumers. Future studies are needed to better evaluate the sources of AMR bacteria in wildlife.